Ameliorative effects of Liv-52 on doxorubicin-induced oxidative damage in rat liver - Yildirim, Nilgun; Lale, Azmi; Yazici, Gulce Naz; Sunar, Mukadder; Aktas, Mehmet; Ozcicek, Adelet; Suleyman, Halis (Taylor & Francis Ltd, 2022)
Hepatotoxicity is a common side effect of doxorubicin (Dox) treatment of cancer. Liv-52 is an ayurvedic medicine that is reported to ameliorate liver injury due to oxidative stress. We investigated the effects of Liv-52 on Dox induced oxidative damage to liver tissues of rats using biochemical and histopathological techniques. Thirty male rats were assigned randomly into three equal groups: control (CG), Dox group (DG) Liv-52 + Dox group (LD). Rats in the LD group received 50 mg/kg Liv-52 in distilled water via gastric gavage. Distilled water was given via the same route to the rats in the DG and CG groups. Rats in the LD and DG groups were injected intraperitoneally with 5 mg/kg Dox 1 h after administration of Liv-52 or distilled water. The procedure was repeated daily for 7 days. On day 8, the animals were sacrificed, and serum and tissue biochemical and histopathological assays were performed. The malondialdehyde level was increased significantly in the DG group, while glutathione and superoxide dismutase levels were significantly lower in the DG group compared to the LD and CG groups. The highest levels of alanine aminotransferase, aspartate aminotransferase and lactate dehydrogenase were found in the DG group, while the lowest levels were found in the CG group, which exhibited levels similar to those of the LD group. Treatment with Liv-52 prior to Dox treatment reduced the histopathologic changes in the Dox group. Therefore, pre-treatment with Liv-52 protected against Dox induced oxidative stress and hepatotoxicity.
Keywords: Doxorubicin; hepatotoxicity; Liv-52; liver; oxidative stress; rat